2002
DOI: 10.1093/oxfordjournals.rpd.a005868
|View full text |Cite
|
Sign up to set email alerts
|

Mechano and Thermoluminescence of Gamma-irradiated CaSO4:Dy Phosphor

Abstract: In order to have a better idea of the interaction of the defect centres produced by y-irradiation with dislocation in the processes of deformation destruction, mechanoluminescence (ML) and thermoluminescence (TL) of gamma-irradiated CaSO4:Dy, these phosphors have been investigated. CaSO4:Dy phosphors were prepared by dissolving CaSO4.2H2O in sulphuric acid and evaporating the excess acid around 300 degrees C. ML was excited impulsively by dropping a load on to the sample. Two peaks have been observed in the ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…On the basis of ESR and step annealing measurements, Nair et al (13) have concluded that the TL peak (∼110 • C) is closely related to SO − 4 defect centres. In the TL glow curves of CaSO 4 :Dy phosphors, only one peak is observed at around 220 • C and two peaks close to each other are observed in the ML intensity against time curve (7). In the TL glow curves of CaSO 4 :Eu phosphors, in addition to a dosimetric peak at 210 • C, another sharp and sensitive TL peak occurs at 110 • C. Hence, we expect that the defect centres corresponding to the 110 • C TL peak play an important role in the ML excitation process.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…On the basis of ESR and step annealing measurements, Nair et al (13) have concluded that the TL peak (∼110 • C) is closely related to SO − 4 defect centres. In the TL glow curves of CaSO 4 :Dy phosphors, only one peak is observed at around 220 • C and two peaks close to each other are observed in the ML intensity against time curve (7). In the TL glow curves of CaSO 4 :Eu phosphors, in addition to a dosimetric peak at 210 • C, another sharp and sensitive TL peak occurs at 110 • C. Hence, we expect that the defect centres corresponding to the 110 • C TL peak play an important role in the ML excitation process.…”
Section: Resultsmentioning
confidence: 90%
“…In most of the materials, only one peak is observed in the ML intensity against time curve, and the ML emission stops as soon as the deformation is interrupted (11). In the ML glow curve of CaSO 4 :Dy phosphors, two peaks close to each other are observed (7), and it is believed that the fist peak is attributed to the ML produced due to charging of the newly created surface and the second peak is due to the release of carriers from the shallow traps, which takes place later on due to the thermal vibration of the lattice. The occurrence of the second and third peaks in the ML glow curve of CaSO 4 :Eu phosphors indicates that some of the carriers excited by mechanical action have transferred to two types of shallow traps, having different traps depth.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Meyer and Winnacker [12] have reported the ML and thermoluminescence in c-irradiated KCl crystals. The ML intensity of coloured alkali halide crystals and CaSO 4 :Dy phosphor increases with gamma rays dose given to them [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…11 Contudo, cabe ressaltar que ainda existem a sonoluminescência, [25][26][27][28] a mecano-ou tribulominescência, [29][30][31][32][33][34] a radioluminescência, [35][36][37][38] a termoluminescência, 34,39,40 a bioluminescência, 41 entre outros. Nesta revisão, serão abordados trabalhos envolvendo a determinação de fármacos baseados em fenômenos fotoluminescentes e quimiluminescentes.…”
Section: Introductionunclassified